2020
DOI: 10.3389/fcell.2020.604026
|View full text |Cite
|
Sign up to set email alerts
|

Rbm24a Is Necessary for Hair Cell Development Through Regulating mRNA Stability in Zebrafish

Abstract: Hair cells in the inner ear and lateral lines are mechanosensitive receptor cells whose development and function are tightly regulated. Several transcription factors as well as splicing factors have been identified to play important roles in hair cell development, whereas the role of RNA stability in this process is poorly understood. In the present work, we report that RNA-binding motif protein 24a (Rbm24a) is indispensable for hair cell development in zebrafish. Rbm24a expression is detected in the inner ear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 74 publications
(90 reference statements)
0
21
0
Order By: Relevance
“…SMPX is a small muscle protein located in the nucleus. It has been reported to be involved in the formation of hearing ( 76 ), but it has not been reported in tumor studies. In this study, we also found that the high expression of these seven genes is related to a poor prognosis in gastric cancer patients, and based on this and previous reports, we speculate that these seven genes can promote the progression of gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…SMPX is a small muscle protein located in the nucleus. It has been reported to be involved in the formation of hearing ( 76 ), but it has not been reported in tumor studies. In this study, we also found that the high expression of these seven genes is related to a poor prognosis in gastric cancer patients, and based on this and previous reports, we speculate that these seven genes can promote the progression of gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Rbm24 has been identified as a target of ATOH1 and GFI1, key transcription factors required for HC differentiation, through DNA-protein interaction assays and in vivo knockout studies (Cai et al, 2015;Jen et al, 2022). Wholebody deletion of rbm24a in zebrafish embryos disrupted HC morphogenesis and led to hearing and balance deficits (Zhang et al, 2020a;Cheng et al, 2020). Deletion of Rbm24 in 2-monthold mice also resulted in auditory and vestibular dysfunction .…”
Section: Rbm24mentioning
confidence: 99%
“…These defects are correlated with a reduced expression level of several zebrafish orthologs of human deafness genes, including smpx (small muscle protein X-linked), gsdmeb (gasdermin Eb), and otofa (otoferlin a). Further analysis suggests that Rbm24a deficiency leads to reduced stability of the corresponding mRNAs [ 17 , 18 ]. Thus, smpx , gsdmeb , and otofa are possible target mRNAs of Rbm24a for hair cell morphogenesis and function.…”
Section: Rbp-mediated Post-transcriptional Regulation In Inner Ear Ha...mentioning
confidence: 99%